2019
DOI: 10.1155/2019/3162378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Submicroscopic Plasmodium falciparum Parasitaemia on Maternal Anaemia and Low Birth Weight in Blue Nile State, Sudan

Abstract: The aim of the present study was to investigate the prevalence of submicroscopic infections and to assess its impact on maternal anaemia and low birth weight. A cross-sectional study was carried out with 1149 consented pregnant women who delivered at 3 main hospitals in the Blue Nile State, between January 2012 and December 2015. From a matched maternal peripheral, placental maternal side, and cord blood sample, blood films and dried spots were prepared for microscopic examination and nested polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Previous studies have pointed out that pregnant women often have low parasite densities, and the use of highly sensitive diagnostic methods such a DNA polymerase chain reaction (DNA PCR) (referred to as sub-microscopic placental malaria) has been recommended to enhance detection of placental malaria [6]. Sub-microscopic MiP remains common in most African countries including Tanzania [8][9][10][11], even though there was a 41% reduction of the malaria incidence rate in sub-Saharan Africa for the period of 2000-2015 [12]. The decreasing proportion of individuals presenting with clinical malaria infection over time has been linked with the scale-up of effective malaria interventions including insecticide-treated nets, effective case management, and indoor residual spraying [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have pointed out that pregnant women often have low parasite densities, and the use of highly sensitive diagnostic methods such a DNA polymerase chain reaction (DNA PCR) (referred to as sub-microscopic placental malaria) has been recommended to enhance detection of placental malaria [6]. Sub-microscopic MiP remains common in most African countries including Tanzania [8][9][10][11], even though there was a 41% reduction of the malaria incidence rate in sub-Saharan Africa for the period of 2000-2015 [12]. The decreasing proportion of individuals presenting with clinical malaria infection over time has been linked with the scale-up of effective malaria interventions including insecticide-treated nets, effective case management, and indoor residual spraying [13].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral sub-microscopic malaria is strongly associated with placental malaria and low maternal hemoglobin levels [14,15], but there are contradictory findings about the association between placental malaria and adverse pregnancy outcomes [11,16,17]. Cottrell et al [16] found that sub-microscopic malaria infection during early pregnancy was associated with adverse pregnancy outcomes, whereas infection detected at delivery in the placenta and peripheral blood sample was not.…”
Section: Introductionmentioning
confidence: 99%
“…7 Such "submicroscopic" infections are present across a range of different settings and populations 5,9-8 11 . Although rarely causative of severe symptoms, they have been associated with a number of adverse 9 outcomes during pregnancy 12,13 , as well as mild anaemia 14 and other symptoms (vomiting, jaundice 10 etc.) in children under 10 15 .…”
mentioning
confidence: 99%
“…There was no evidence of systematic differences in the PCR and 11 microscopy methodologies in different transmission archetypes (Supp Fig.6) and the observed results 12 were robust to the choice of High/Low threshold (Supp Fig.7). 13 Integrating these results with estimates of comparative submicroscopic infectivity to mosquitoes, we 14 estimate that in transmission settings characterised by historically low levels of transmission, 15 submicroscopically infected individuals could account for 17.5% to 68.0% of onwards transmission in 16 low prevalence settings (defined as <= 5% survey prevalence by PCR), depending on the assumption 17 surrounding the comparative infectivity of microscopically detectable and submicroscopic infections 18 (Fig.7C). By contrast, our results suggest the contribution of the submicroscopic reservoir to 19 transmission is less important in settings where transmission has only recently declined (Fig.7B) 20 although their contribution is not irrelevant, ranging from 7.8% to 46.0% depending on the assumed 21 comparative infectivity.…”
mentioning
confidence: 99%
“…The prevalence of submicroscopic malaria infection among pregnant women in the current study was considerable. Other studies have found wide spread submicroscopic malaria infections [ 47 49 ]. Many asymptomatic infections are submicroscopic and can only be detected by molecular methods.…”
Section: Discussionmentioning
confidence: 99%